Rereading the New Criticism - Hickman, Miranda B., 1969-; McIntyre, John D., 1966- (Book collections on Project MUSE., 2012)
"Committed to rigorous 'close reading' and engagement with the 'text itself' rather than information 'extrinsic' to the text, John Crowe Ransom and a group of colleagues in the American South of the 1930s established a vanguard approach to literary criticism they called the'New Criticism.' By the 1940s, New Critical methods had become the dominant pedagogy in departments of English at colleges and universities across America, enjoying disciplinary hegemony until the late 1960s, when an influx of new theoretical work in literary studies left the New Criticism in shadow. Inspired by a range of new commentary reconsidering the New Criticism (from critics including Jane Gallop, Terry Eagleton, Charles Altieri, and Camille Paglia), the essays in Rereading the New Criticism reevaluate the New Critical corpus, trace its legacy, and explore resources it might offer for the future of theory, criticism, and pedagogy. Addressing the work of New Critics such as Ransom, Cleanth Brooks, and Robert Penn Warren, as well as important forerunners of the New Critics such as I.A. Richards and William Empson, these ten essays shed new light on the genesis of the New Criticism and its significant contributions to the development of academic literary studies in North America; revisit its chief arguments and methods; interrogate received ideas about the movement; and consider how its theories and techniques might inform new methodologies for literary and cultural studies in the twenty-first century"--Publisher's description